Mosque Dualism: The Function of The Mosque As A Place Of Worship And The Function of The Mosque As A Place of Social-Islamic Educational Activities - Muhammad Sa'i (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The existence of mosques, both seen in historical, epistemological, and sociological aspects, was born at the same time as the preaching of the Prophet Muhammad (peace be upon him), functioning as a centre of worship and civilization of Muslims. Public awareness of building mosques is very high in spirit on the island of Lombok, which is referred to as the island of a thousand mosques. However, this enthusiasm often does not go hand in hand and side by side, so it is found that many mosques only function as places of worship for mahḍah. In contrast, mosques serve as places of Islamic social-educational activities and are quiet without worshippers, like luxury houses without residents. This article describes the construction of two mosques in one neighbourhood, the impacts and solutions, and how it functions as a place of worship and Islamic social-educational activities. The data in this article was extracted from observations made in several areas of Dasan Cermen, Karang Bedik-Punia, Karang Baru, and Babakan. Furthermore, information mining was carried out through in-depth interviews with religious leaders, community leaders, mosque administrators, and the Government. Based on the data obtained, it is concluded that the motives for building mosques, seen from their functions, are 1) as a place of mahdah worship, namely the construction of mosques to the needs of worshippers to worship; 2) as a social place of society, namely a) the integration of society and even making the community more robust and more solid; and b) with the construction of mosques, it causes social conflict and disintegration, namely (1) pseudo-groups that have the same interests; (2) essential groups represented by supporters of the existence of the second mosque and the third mosque; (3) conflict groups represented by the third support group, and 3) as a place for Islamic education activities, namely mosques used by the community to study the Qur'an and study Islamic knowledge, although not yet maximized due to conflicts in the construction of two mosques in one neighbourhood.